Limit Condition for Anisotropic Materials with Asymmetric Elastic Range - OSTROWSKA–MACIEJEWSKA, Janina; PĘCHERSKI, Ryszard Bolesław; SZEPTYŃSKI, Paweł (Engineering Transactions, 2012)
In the paper a new proposition of an energy-based hypothesis of material effort is intro- duced. It is based on the concept of influence functions introduced by Burzyński [3] and on the concept of decomposition of elastic energy density introduced by Rychlewski [18]. A new proposition enables description of a wide class of linearly elastic materials of arbitrary symmetry exhibiting strength differential effect.